The Namaste Club : a novel - Elias, Asha (William Morrow, 2025)
"From the author of Pink Glass Houses, another delicious beach read about rich people behaving badly! The Yoga Retreat is sly and hilarious send-up of the wellness industrial complex, rich ladies doing yoga, and all things fabulous and Florida"--